Pengembangan Buku Ajar Pengenalan Lingkungan Lahan Basah untuk Paud Jilid 2 - Wahyudi, Muhammad Dani; Safitri, Hana Ika Safitri; Rahmaniah, Nahdia Fitri; Muzdalifah, Fithrii; Fashlah, Anggita Gunati (LPPM Institut Pendidikan Nusantara Global, 2025)
Developing a reading habit from an early age is very beneficial for increasing children's insight and knowledge. This habit can be fostered through books, including textbooks. Textbooks can be used to introduce about wetland to early childhood. This introduction to the environment Introduction to the environment, especially wetland environments, fosters a sense of environmental concern in children, and also fosters awareness of love for the environment. The development of a wetland introduction textbook is well-designed, using language that is easy for children to understand and including images to facilitate children's understanding of the information. The type of research used in this study is research and development (R&D). The development model that will be used in the textbook is ADDIE development, namely Analysis, Design, Development, Implementation, and Evaluate. The experiment was conducted several times, involving 15 children of A Kindergarten in the South Kalimantan area. In addition to A Kindergarten children, this study also involved 2 teachers and even involved a materials expert and a media expert to get a good textbook that is appropriate to the development of early childhood. Based on the results of the textbook trial, the increase in children who know the means of transportation and types of work in the wetland environment reached 40%, from initially only 5 children to 11 children who know about the means of transportation and types of work in the wetland environment. The results of the study show that the textbook is effective in introducing the wetland environment to early childhood. The textbook also got a positive response from teachers and parents.